Systematic studies of the structural and optoelectronic characteristics of CaZn2X2 (X = N, P, As, Sb, Bi). (8th January 2018) - Murtaza, G; Yousaf, Naveed; Yaseen, M; Laref, A; Azam, Sikander
Abstract: Structural, electronic and optical properties of CaZn2 X2 (X = N, P, As, Sb, Bi) Zintl compounds are investigated using all electrons full potential linearized augmented plane wave method. The unit cell volume of the compounds is optimized by generalized gradient approximation (GGA). For electronic and optical properties modified Becke Johnson exchange potential alongwith the GGA is used. It is observed that the band gap decreases by changing the anion X from N to Bi. All compounds show band gap except CaZn2 Bi2 compound, which show metallicity. We have thoroughly discussed the absorption coefficient, optical conductivity, refractive index, birefringence and reflectivity. Static value of refractive index shows inverse variation with band gap. These Zintl compounds reveal strong interband transitions in the visible and ultraviolet energy regions.